Proses Pembuatan Briket Arang dari Limbah Batang Singkong dengan Menggunakan Perekat Organik - Yunitha Belak, Ofriana; Abrina Anggraini, Sinar Perbawani; Iskandar, Taufik; Grazias, Kostadia (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2019)
The development of cassava stem waste from year to year is increasing and the utilizationof cassava stem waste is not optimal because only 10% of the cassava stem height used forreplanting with the remaining 90% is not utilized at all. This study aims to utilize cassava stemwaste into charcoal briquettes as an alternative fuel by carbonizing or fabricating using fastpyrolysis reactors at 350 Â° C for 4 hours to produce charcoal. Charcoal that has been formedis mixed with starch adhesives, molasses and cow dung with concentrations of 5, 10, and 15%and printed using a hydrolic press. The analysis results obtained, the value of water content(0.0015%), ash content (0.0212%), volatile matter values (2.33824%), heating value (7.184 cal/ g), combustion rate (46:52) and fixed carbon (98,0159%). Based on the results of the analysis,the optimal value of making charcoal from cassava stem waste is found in cow dung adhesive.